Home Medication Review among Patients with Chronic Diseases in Rural Villages of Pahang, Malaysia: A Case Report - Norny Syafinaz Ab Rahman; Nur Alyaa Anisa Mat Harom; Nor Ilyani Mohamed Nazar (Journal of Pharmacy)
Introduction: Home Medication Review (HMR) is crucial for optimising medication use and improving patient’s outcomes. Despite its potential benefits, HMR implementation in rural areas faces challenges. This study evaluates the impact of HMR programs on patients with chronic diseases in a rural setting, addressing challenges and proposing strategies for improvement. Case Presentations: This case report presents two cases involving patients with chronic diseases residing in a rural area of Pahang, Malaysia, who participated in pharmacist-led HMR visits. The first case describes a 62-year-old single Malay female with multiple chronic conditions, including Type 2 diabetes mellitus (T2DM), hypertension, dyslipidemia, and bronchial asthma, managed with eight prescribed medications. The second case involves a 34-year-old married Malay female diagnosed with hypertension and T2DM, receiving nine prescribed medications. Both patients underwent a follow-up HMR visit six months after the initial consultation. During each visit, assessments included blood pressure (BP), pulse rate (PR), and blood glucose tests. HMR activities encompassed medication reconciliation, review, patient interviews, evaluation of medication knowledge and adherence, inspection of medication storage, and patient counseling. Identified drug-related problems (DRPs) were addressed through appropriate interventions. Results: The study reveals improved patient understanding post-HMR and emphasising the role of pharmacists in addressing medication-related issues. Challenges like non-adherence, uncontrolled disease conditions, and incorrect insulin storage persist. The discussion explores these challenges, citing the need for patient education, regular follow-ups, multidisciplinary collaboration, and technology integration to enhance patient outcomes. Summary: These cases underscore the challenges of managing chronic diseases in resource-limited rural settings and highlight the critical role of pharmacist-led HMR in optimizing medication use and improving patient outcomes. The findings highlight the importance of regular follow-up, tailored interventions to address drug-related problems, and collaborative care approaches. They also advocate for integrating technology, enhancing patient education, and addressing social determinants to improve medication understanding and overall health outcomes in underserved populations.